A sorkatonaság munkaerőpiaci hatásai Magyarországon; The effect of compulsory military service in Hungary - Háló Buda; Reizer Balázs (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
– We investigate the effect of compulsory military service on wages in Hungary. We use administrative social security data and difference-in-difference strategy to estimate how the conscription in 2003 and 2004 affected the wages of soldiers. Before conscription, the soldiers earned 20 percent less than similar workers who were not conscripted later. This gap disappears after the military service and former soldiers earned 3 percent more than similar workers who did not served in the army. As the compulsory military service was only 6 months we do not think that the wage growth was driven solely by the increase of productivity. Instead we argue that workers were discriminated before conscription or the match value was very low between soldiers and firms before the conscription.
Keywords: J00; J31; J40; 330; Compulsory military service; Labor demand; Wage Differentials